A ragged porous hollow tubular carbon nitride towards boosting visible-light photocatalytic hydrogen production in water and seawater. (April 2022) - Guo, Feng; Chen, Zhihao; Shi, Yuxing; Cao, Longwen; Cheng, Xiaofang; Shi, Weilong; Chen, Lizhuang; Lin, Xue
Abstract: Photocatalytic water splitting to produce hydrogen, especially seawater, shows great economic value and development prospects to deal with the energy crisis. In this paper, urea and melamine were employed as base precursor materials to obtain four different morphologies of tubular g-C3 N4 : stacked rectangular thin plates with flocculent structure, ragged porous hollow tubes, porous hollow tubes and tetragonal hollow prismatic tubes by simply regulating the heating rate. Among them, the ragged porous hollow tubular g-C3 N4 (TCN-1.5) exhibit an amazing hydrogen evolution rate of 8683 μmol h −1 g −1 from water, which is 19.3 times that of the massive g-C3 N4 (449 μmol h −1 g −1 ), and still maintain a high hydrogen evolution rate (6782 μmol h −1 g −1 ) from sea water. The analysis results show that by controlling the change of the heating rate, the ammonia overflow rate can be effectively controlled to produce abundant voids and pits to form volume defects, which can exhibit higher specific surface area and serve as a highly active center for the catalytic reaction and effectively improve the photocatalytic performance. This study provides a simple design idea to construct a novel type of ragged porous hollow tubular g-C3 N4 for efficient photocatalytic hydrogen production from water and seawater.